Success of the 4 Pillars Toolkit for Influenza and Pneumococcal Vaccination in Adults. Issue 6 (18th June 2013) - Nowalk, Mary Patricia; Nolan, Beth A. D.; Nutini, Jean; Ahmed, Faruque; Albert, Steven M.; Susick, Michael; Zimmerman, Richard K.
Abstract Background Standing order programs (SOPs) allowing nonphysician personnel to assess patients' immunization status and administer vaccines without an individual physician order are a proven method of increasing adult vaccinations, yet they are underutilized by primary care physicians. Methods In a before‐and‐after trial, a pilot‐tested and revised SOP toolkit (4 Pillars Toolkit) was implemented in four diverse primary care practices. Changes in influenza and pneumococcal polysaccharide vaccine (PPSV) vaccination rates were measured. The toolkit was evaluated using direct observation, group interviews, and surveys of each practice's staff. Results Use of the 4 Pillars Toolkit varied across sites. PPSV rates increased significantly overall for high‐risk adults (18–64 years; 25% in 2010–2011 vs. 40% in 2011–2012, p = .02) but not for older adults (≥65 years; 44% vs. 52%, p = .26) and in two of four practices among both high‐risk and older adults (p < .05). Influenza vaccination rates increased significantly in three of four sites and overall (22% in 2010–2011 vs. 33% in 2011–2012, overall; p < .001). Practices more fully implementing the toolkit demonstrated larger increases in vaccination rates. Conclusions The 4 Pillars Toolkit is a promising means of improving primary care practice across diverse settings, with better results observed when strategies were maximally utilized.